2006
DOI: 10.4314/eamj.v83i1.9345
|View full text |Cite
|
Sign up to set email alerts
|

Millennium development goal 5: a review of maternal mortality at the Kenyatta National Hospital, Nairobi

Abstract: Objectives: To review if there is a change in the maternal mortality rate at the Kenyatta National Hospital since the inception of the Millennium Development Goal strategy in 1990, compared to earlier reviews. Design: A retrospective descriptive study. Setting: Kenyatta National Hospital. Subjects: Maternal deaths attributed directly to obstetric causes. Main outcome measures: Determination of maternal mortality rates of all patients admitted to the Kenyatta National Hospital Maternity and died after admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 5 publications
6
15
0
Order By: Relevance
“…This was in agreement with findings in the study in Kenyatta National Hospital [10]. The highest proportion of mothers had attended two antenatal visits or less with slightly more having attended two visits and a fifth having not attended any visit.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was in agreement with findings in the study in Kenyatta National Hospital [10]. The highest proportion of mothers had attended two antenatal visits or less with slightly more having attended two visits and a fifth having not attended any visit.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the findings from a study in Moi Teaching and Referral hospital where a retrospective audit of 150 maternal deaths that had been recorded from 2004 to 2011 revealed that majority of the deaths had occurred in women between 25 and 34 years [9]. Similarly, a study at Kenyatta National Hospital among 253 maternal deaths found two-thirds of the women to have been between 25 and 35 years of age [10]. The study by Juma et al, 2000, revealed that the deaths were mainly from the 14 to 24 years age group.…”
Section: Discussionsupporting
confidence: 87%
“…Most cesarean section are performed as emergency procedures with an elective rate of less than 4%. [6][7][8][9] The advantage of placing a subcutaneous drain to drain any blood or serous fluid that may accumulate in the subcutaneous space, which cause post-operative pain or provide a good medium for microbial growth and infection. 10 Some surgeons, however, have raised much argument about the value of subcutaneous drains.…”
Section: Introductionmentioning
confidence: 99%
“…The ratios are higher for the major teaching and referral hospitals where obstetrics complications are concentrated. For example, the MMR in Kenya’s largest referral hospital, Kenyatta National Hospital (KNH), was 922 per 100,000 live births in 2004 [8]. In Kilifi District Hospital in Kenya, the MMR was 250 per 100,000 live births between 2008 and 2010 [9].…”
Section: Introductionmentioning
confidence: 99%